If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(11r + -13) = 7r + 57 + 32r Reorder the terms: 3(-13 + 11r) = 7r + 57 + 32r (-13 * 3 + 11r * 3) = 7r + 57 + 32r (-39 + 33r) = 7r + 57 + 32r Reorder the terms: -39 + 33r = 57 + 7r + 32r Combine like terms: 7r + 32r = 39r -39 + 33r = 57 + 39r Solving -39 + 33r = 57 + 39r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-39r' to each side of the equation. -39 + 33r + -39r = 57 + 39r + -39r Combine like terms: 33r + -39r = -6r -39 + -6r = 57 + 39r + -39r Combine like terms: 39r + -39r = 0 -39 + -6r = 57 + 0 -39 + -6r = 57 Add '39' to each side of the equation. -39 + 39 + -6r = 57 + 39 Combine like terms: -39 + 39 = 0 0 + -6r = 57 + 39 -6r = 57 + 39 Combine like terms: 57 + 39 = 96 -6r = 96 Divide each side by '-6'. r = -16 Simplifying r = -16
| 4+3x=x+14 | | x+15=10+16.45 | | 48-48-3(x-4)=3x | | -y-1=2y-16 | | 9x^2-45x+36=0 | | 3-0.25x=-0.5x+9 | | 75-2q=-15+4q | | -21+5(8-4)= | | .90+19x=18x | | 6x^2-54x+120=0 | | 2x-3=-3x-2 | | 2(7x-2)+7(-8-x)=-2+5+2x+5 | | 15m+4-9x=13 | | 126=-9(v-4)-9v | | 2p+11=73 | | (5y)(-2)=(-2)(5y) | | 16y-13=72-14y | | -32-3x=2(2+8x)-x | | 6*2+3y=15 | | -8v-3=-5v+3 | | 3y+(15x+75)=180 | | -5y(x-3)=-25 | | x(x+3)=9 | | -2(2x-1)+3=9 | | 5-2p= | | 5x-5=3x+13 | | 12a+12+5a-9= | | 8a=860 | | 9w-17.9=-2.3 | | x^3-16x^2-216x+896=0 | | z=9y+3yx | | 2(-2x-1)+3=9 |